A inclusão de alunos surdos no 6º ano do Ensino Fundamental na E.M.E.I.E.F Jardim do Ouro do município de Itaituba-PA - PESSOA, Alesandro dos Santos (2021)
The present work entitled "The process of inclusion of deaf students in the 6th year of primary education in a school in the municipality of Itaituba - Pará" aims to analyze how the process of inclusion of deaf students in the series in focus occurs. We seek to understand the difficulties faced by regular teachers and specialized teachers who accompany deaf students in the common room (caretaker); identify the methodologies applied by teachers; to investigate the forms that contemplate bilingual instruction in the common / regular room, even if the teachers do not have specific training for the Brazilian Sign Language (LIBRAS) and know the pedagogical work developed by them. The methodology of the work involved qualitative research with a descriptive basis. The data collection instruments involved questionnaires that were applied to the teachers: a common room teacher, a physical education teacher and a teacher carer. The work involved a bibliographical survey and field research to confront theory and practice. The analysis of current legislation on inclusion was of fundamental importance and involved several authors in the area: Bisbo (2016), Brazil (1996), Dessen (1997), Lacerda (1996), Lopes (2013), Lima 2010), in addition to other authors who contributed directly to the theme in question. The results will be analyzed and treated.